Irupsi Generasi Beriman Digital Z dan Disrupsi Katekese Kebangsaan - Andalas, Mutiara (STF Driyarkara - Diskursus, 2022)
This paper discusses the irruption of the digital faithful generation of Z in the Indonesian Catholic church and its disruption to citizenship catechesis. The discussion of citizenship catechesis will fall short if we still fixate on the classic definitions of catechesis, the method of catechesis, and the profile of catechists in the apostolic exhortation Cateceshi Tradendae (1979). The predigital world conditions ideas about them. An in-depth discourse on citizenship catechesis needs to depart from the digital faithful generation of Z irrupting in the Indonesian Catholic Church. 'Irruption', according to the liberation theologian Gustavo Gutiérrez, refers to the presence of people who previously lived at the underside of history. Previously being absented, they transform into the subject of history. Irruption is also an ecclesial process. The generation of Z has emerged in the history of the Indonesian Catholic church as homo religiosus digitalis. They bring the disruptive spirit of the digital era to the body of the Catholic church. As digital integrators, they are open to incorporating faith in their lives. Based on their autobiography, homo religiosus digitalis Z lives a connective pedagogy with distinctive characteristics from predigital believers. Their irruption shakes the identity of the catechist and their vocation to